Supporting Research and Data Analysis in NASA's Science Programs: Engines for Innovation and Synthesis - National Research Council; Division on Engineering and Physical Sciences; Commission on Physical Sciences, Mathematics, and Applications; Space Studies Board; Task Group on Research and Analysis Programs (The compass series, 1998)
Effective science, clearly a mandate for the National Aeronautics and Space Administration (NASA), involves asking significant questions about the physical and biological world and seeking definitive answers. Its product is new knowledge that has value to the nation. NASA's flight projects are highly visible and usually the most costly elements of this process, but they are only a part of the science enterprise. Flight projects are founded on research that defines clear scientific goals and questions, designs missions to address those questions, and develops the required technologies to accomplish the missions. This research is funded primarily by NASA's research and analysis (R&A) programs. Data from flight projects are transformed into knowledge through analysis and synthesis-research that is funded both by R&A and by the data analysis (DA) portion of mission operations and data analysis (MO&;DA) programs. R&A and DA programs are the subject of this report and are grouped for convenience under the heading of research and data analysis (R&DA).